Advancements in the Protocol for Rate of Force Development/Relaxation Scaling Factor Evaluation - Smajla, Darjan; Žitnik, Jure; Šarabon, Nejc (Frontiers in Human Neuroscience, 2021)
Brief submaximal actions are important for wide range of functional movements. Until now, rate of force development and relaxation scaling factor (RFD-SF and RFR-SF) have been used for neuromuscular assessment using 100–120 isometric pulses which requires a high level of attention from the participant and may be influenced by physiological and/or psychological fatigue. All previous studies have been conducted on a smaller number of participants which calls into question the eligibility of some of the outcome measures reported to date. Our aims were: (1) to find the smallest number of rapid isometric force pulses at different force amplitudes is still valid and reliable for RFD-SF slope (kRFD–SF) and RFR-SF slope (kRFR–SF) calculation, (2) to introduce a new outcome measure – theoretical peak of rate of force development/relaxation (TPRFD and TPRFR) and (3) to investigate differences and associations between kRFD–SF and kRFR–SF. A cross-sectional study was conducted on a group of young healthy participants; 40 in the reliability study and 336 in the comparison/association study. We investigated the smallest number of rapid isometric pulses for knee extensors that still provides excellent reliability of the calculated kRFD–SF and kRFR–SF (ICC2,1 ≥ 0.95, CV < 5%). Our results showed excellent reliability of the reduced protocol when 36 pulses (nine for each of the four intensity ranges) were used for the calculations of kRFD–SF and kRFR–SF. We confirmed the negligibility of the y-intercepts and confirmed the reliability of the newly introduced TPRFD and TPRFR. Large negative associations were found between kRFD–SF and kRFR–SF (r = 0.502, p < 0.001), while comparison of the absolute values showed a significantly higher kRFD–SF (8.86 ± 1.0/s) compared to kRFR–SF (8.03 ± 1.3/s) (p < 0.001). The advantage of the reduced protocol (4 intensities × 9 pulses = 36 pulses) is the shorter assessment time and the reduction of possible influence of fatigue. In addition, the introduction of TPRFD and TPRFR as an outcome measure provides valuable information about the participant’s maximal theoretical RFD/RFR capacity. This can be useful for the assessment of maximal capacity in people with various impairments or pain problems.